2018
DOI: 10.13175/swjpcc150-17
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sleep duration and weekend oversleep on body weight and blood pressure in adolescents

Abstract: Introduction Weekend oversleep or catchup sleep is a frequent occurrence in children, but there are relatively little data concerning its impact on weight and blood pressure. The aim of this study was to assess the association between sleep duration and oversleep, and weight and blood pressure in adolescents. Methods Sleep duration, weight and blood pressure of 327 children (51.4% boys, mean age 13.3 ± 1.7 years) who had polysomnograms performed during both exam cycles of the Tucson Children’s Assessment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Sleep and circadian rhythm disorders, including delayed sleep, are associated with poor mental health. 4,5,[34][35][36][37][38][39] We found higher rates of delayed sleep time among African-American adults compared to whites in a community-based cohort. The average weekday sleep duration among African Americans was on average 22 minutes shorter than that for whites.…”
Section: Discussionmentioning
confidence: 56%
“…Sleep and circadian rhythm disorders, including delayed sleep, are associated with poor mental health. 4,5,[34][35][36][37][38][39] We found higher rates of delayed sleep time among African-American adults compared to whites in a community-based cohort. The average weekday sleep duration among African Americans was on average 22 minutes shorter than that for whites.…”
Section: Discussionmentioning
confidence: 56%
“…It was not within the scope of this study to investigate differences in sleep patterns during quarantine to conduct a comparison with pre-pandemic sleep preferences. So it was difficult to differentiate between the normal recommended sleeping hours that help students to reduce tension, regulates mood, improves concentration and memory (Carley & Farabi, 2016 ), and oversleeping that had negative health impacts on students, like cognitive impairment, depression, risk of obesity, diabetes, and heart diseases (Quan et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Quan et al consider short sleep duration as an important behavioral factor that affects blood pressure in children and adolescents. 40 In the meta-analysis of Jiang et al, 41 the Odds Ratio (OR) of the grouped data indicated that short sleep duration was associated with the risk of high blood pressure (OR=1.51; 95% confidence interval [95% CI] 1.04-2.19, random effects model), mainly in male adolescents (OR = 1.55; 95%CI 1.24-1.93, random effects model). 41 …”
Section: Discussionmentioning
confidence: 99%